2022
DOI: 10.1002/jmri.28215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Anti‐PD‐1 Therapy on Triple‐Negative Breast Cancer in Mice by Diffusion Kurtosis Imaging and Dynamic Contrast‐Enhanced Imaging

Abstract: Background The monitoring of immunotherapies is still based on changes in the tumor size in imaging, with a long evaluation period and low sensitivity. Purpose To investigate the effectiveness of diffusion kurtosis imaging (DKI) and dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) in assessing the therapeutic efficacy of anti‐programmed death‐1 (PD‐1) therapy in a mouse triple negative breast cancer (TNBC) model. Study Type Prospective. Animal Model A total of 54 BALB/c mouse subcutaneous 4 T1 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
3
4
0
Order By: Relevance
“…S8 shows standard dMRI metrics, namely ADC and kurtosis excess 𝐾𝐾, in the same mouse livers. Visual trends highlight that the higher cell density of sample Patinf1 translated to remarkably reduced ADC and increased 𝐾𝐾 compared to the Control, is in line with known correlations with cellularity (38,39). Lastly, Fig.…”
Section: Computer Simulations Confirm Model Selection From Actual Mri...supporting
confidence: 80%
“…S8 shows standard dMRI metrics, namely ADC and kurtosis excess 𝐾𝐾, in the same mouse livers. Visual trends highlight that the higher cell density of sample Patinf1 translated to remarkably reduced ADC and increased 𝐾𝐾 compared to the Control, is in line with known correlations with cellularity (38,39). Lastly, Fig.…”
Section: Computer Simulations Confirm Model Selection From Actual Mri...supporting
confidence: 80%
“…Tang and colleagues compared an antiprogrammed death receptor-1(PD-1) therapy group with a control group in a triple negative breast cancer mouse model and found significant differences in K and ADC 0 between the two groups at 5 and 10 days after treatment. 26 Additionally, ADC 0 was significantly different between the two groups at 15 days after treatment and correlated positively with histological CD45 levels, suggesting immune effects. 26 …”
Section: Treatment Evaluationmentioning
confidence: 90%
“… 26 Additionally, ADC 0 was significantly different between the two groups at 15 days after treatment and correlated positively with histological CD45 levels, suggesting immune effects. 26 …”
Section: Treatment Evaluationmentioning
confidence: 90%
“…DKI can be calculated from standard DWI-acquired data, after additional post-processing that is not currently included in standard MRI software [78]. The potential benefits of this technique for immunotherapy monitoring were reported in several recent studies, including on dendritic cell treatment [79], and anti-PD-1 ICI monitoring [80]. A recent study of DKI in metastatic melanoma patients reported that cell death can be detected as early as 3-12 weeks after treatment initiation [81].…”
Section: Advanced (Non-molecular) Mrimentioning
confidence: 99%